The Influence of Mason Group Composition on Optimal Field Labor’s Productivity in Malang – East Java - Tjaturono Tjaturono (IPTEK The Journal for Technology and Science, 2009)
The composition of labor groups is one of the main factors determining their productivity. So far, in Indonesia the labor composition is based on both the Indonesian National Standard (Standar Nasional Indonesia/ SNI) of 2001 and the result of housing developers’ 'trial and error test'. However, these compositions do not produce an optimal productivity. This study is aimed at obtaining an ideal composition of a labor group and equivalent coefficient as well as actual productivity differences on productivity of the SNI 2001. The method used are field observation and interview on 260 labors from a group of the middle-class house's construction in Malang – East Java. The data obtained were processed by using descriptive statistics and statistical test for mean differences. The results of this research show that the ideal compositions of masonry foundation and bricklaying labors are: 1 mason: 2 labors, and 1 mason: 1½ labors for wall plastering. The equivalent coefficients for various mason groups are also obtained. Compared with the actual productivity of SNI 2001, the field labors’ productivities are 108, 5%, 19%, and 155% for masonry foundation, bricklaying, and wall plastering, respectively